Perancangan Prototype Mesin Pembersih kabel transmisi listrik berbasis internet - Shintya Adhe Putri; a asni b; aswadul fitri saiful rahman (Jurnal Teknik Elektro Uniba (JTE UNIBA), 2019)
This research on the tittle “ DESIGNING PROTOTYPE CLEANING MACHINE IN INTERNET- BASED ELECTRIC TRANSMISSION CABLE “ this theses to eassly cleaning lines transmission cable from the dirt of lines cable transmission used by Arduino UNO, as a first component, L298N as a Driver Motor Electric fuction to movers motor dynamo. This tools have a cleaning can cleaning at line cable transmission with the mover cutting motor dynamo, that tools cutiing direct clockwise and the opporside.Based on the tool teste of cutting materials made from arcylyric its not efisiens on cutting all the hard dirt concern at transmission cable. While of the materials made from grinda is more efisien in cutting and concern hard dirt at transmission cable .